Pneumococcal Capsular Polysaccharide Preparations May Contain Non-C-Polysaccharide Contaminants That Are Immunogenic - Yu, Xinhong (American Society for Microbiology, 1999)
We measured the capacity to opsonize Streptococcus pneumoniae serotype 6B and estimated the concentration of immunoglobulin G anti-6B capsular polysaccharide (PS) antibodies in 25 pre- and postimmune sera from adults immunized with a pneumococcal PS vaccine. We first studied two postvaccination serum samples displaying less opsonophagocytic capacity than expected. The majority of anti-6B antibodies in the two samples reacted with the capsular PSs of several unrelated serotypes (2, 4, 9V, 19F, and 23F) and with the lysate of noncapsulated S. pneumoniae bacteria but not with C-PS. The non-type-specific antibodies accounted for at least one-half of anti-6B antibodies in 40% of prevaccination sera and 10% of postvaccination sera from adults. The non-type-specific antibodies could be demonstrated in the enzyme-linked immunosorbent assays (ELISAs) for pneumococcal antibodies to other serotypes (4, 9V, 18C, 19F, and 23F). The nonspecific antibodies appear to bind a contaminant(s) in the current preparations of capsular PS. ELISA for antibodies to pneumococcal capsules may not be serotype specific for some samples.